PREVALENCE OF HELICOBACTER PYLORI INFECTION AMONG YOUTH AGED 15 -30 YEARS SEEKING HEALTH CARE. A PROSPECTIVE CROSS-SECTIONAL STUDY. AT C-CARE INTERNATIONAL HOSPITAL KAMPALA. - Ssewankambo, Shaban; ssegujja, frank; Nalubega, Janefrank (Student's Journal of Health Research Africa, 2024)
Background The study was conducted to determine the prevalence of H. pylori infections among youth aged 15-30 years seeking health care services at C- CARE IHK. The specific objectives were to determine the prevalence, and infection patterns among various age groups and genders and also find out the risk factors influencing the prevalence of H. pylori infections among youth aged 15-30 years attending C- CARE IHK. Methodology A prospective cross-sectional study design using both quantitative and qualitative methods was conducted. A questionnaire was used to collect qualitative data from patients' age, gender, and other relevant data that gathered data to meet and answer the objectives of the study. Prevalence was determined by collecting and testing stool samples using stool H. pylori antigen kits and then results were entered into a result sheet. A convenient way of sampling was used to select eligible participants and a sample size of 88 was obtained. Results Out of the 88 samples analyzed, 47% were positive for H. pylori infection while 53% were negative. The most affected were males at 53.7%, the age group was (25-30) years at 63.4% and the least affected age group was (15-19) years at 12.2%. people living in town (75.6%), people of no level of education (51.2%), alcoholism, and smoking (73.2%,34.1%) were the factors associated with the prevalence of H. pylori infection. Conclusion The prevalence of H. pylori was relatively high, towns and unhygienic conditions predisposed the majority of the patients while the age of 25-30 was affected mostly. Recommendations The Ministry of Health should advocate for the testing of youth for H. pylori infection to put more emphasis on sensitizing youth about how it’s acquired, spread, and prevented and the complications of H. pylori.